2021
DOI: 10.1021/acs.jmedchem.0c02151
|View full text |Cite
|
Sign up to set email alerts
|

Alkyne-Bridged α-Conotoxin Vc1.1 Potently Reverses Mechanical Allodynia in Neuropathic Pain Models

Abstract: Several Conus-derived venom peptides are promising lead compounds for the management of neuropathic pain, with α-conotoxins being of particular interest. Modification of the interlocked disulfide framework of α-conotoxin Vc1.1 has been achieved using on-resin alkyne metathesis. Although introduction of a metabolically stable alkyne motif significantly disrupts backbone topography, the structural modification generates a potent and selective GABA B receptor agonist that inhibits Ca v 2.2 channels and exhibits d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…Designer disulfide mimetics can prevent disulfide bond scrambling and therefore represent powerful tools in disulfide-rich peptide drug discovery . Strategies including dicarba, saturated dicarba, alkyne, thioether, ether, diselenide (Sec), penicillamine-cysteine (Pen-Cys) hybrid, and triazole bridge replacement have been extensively applied in CTx modifications (Figure C). However, such strategies lack broad applicability owing to incompatibility of the mimetic moiety with bioactivity and toxicity. Head-to-tail backbone cyclization is another investigated strategy to improve peptide stability through prevention of degradation as it stabilized the structure and reduced proteolysis susceptibility. Nevertheless, the application of this method to RgIA resulted in obvious potency drop on α9α10 nAChR binding affinity. …”
Section: Introductionmentioning
confidence: 99%
“…Designer disulfide mimetics can prevent disulfide bond scrambling and therefore represent powerful tools in disulfide-rich peptide drug discovery . Strategies including dicarba, saturated dicarba, alkyne, thioether, ether, diselenide (Sec), penicillamine-cysteine (Pen-Cys) hybrid, and triazole bridge replacement have been extensively applied in CTx modifications (Figure C). However, such strategies lack broad applicability owing to incompatibility of the mimetic moiety with bioactivity and toxicity. Head-to-tail backbone cyclization is another investigated strategy to improve peptide stability through prevention of degradation as it stabilized the structure and reduced proteolysis susceptibility. Nevertheless, the application of this method to RgIA resulted in obvious potency drop on α9α10 nAChR binding affinity. …”
Section: Introductionmentioning
confidence: 99%
“…Several studies have indicated that certain α-conopeptides act as agonists of the GABA B receptor resulting in analgesic effects [ 42 , 43 , 44 , 45 ]. This has led to questions regarding the role and necessity of α9-containing nAChRs in mediating α-conopeptide analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…A 3 -macrocyclization could be applicable for developing high-affinity binders for various biological targets. Moreover, the methods described for selective alkyne reduction may be of value for further exploration of cyclic peptide analogues possessing unsaturated cross-linkers. , …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the methods described for selective alkyne reduction may be of value for further exploration of cyclic peptide analogues possessing unsaturated cross-linkers. 40,41 The scavenger receptor CD36 plays roles in the regulation of the TLR2/6 heterodimer assembly, the activation of transcription of proinflammatory cytokines, and the production of NO and reactive oxygen species. 37,42 Cyclic azapeptides offer notable potency for reducing TLR-2 agonist-induced proinflammatory cytokines and chemokines by binding CD36 and inducing dissociation from the TLR complex.…”
Section: ■ Conclusionmentioning
confidence: 99%
See 1 more Smart Citation